(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the pedagogical effectiveness of the case-study (keys-stadi) method in developing professional communicative skills of future teachers. The essence, stages, advantages, and integration of the case-study method with digital technologies are examined. The findings indicate that the case-study approach prepares students to think independently, analyze problematic situations, engage in collaborative work, and develop communicative competencies in real pedagogical contexts. Additionally, the use of digital tools (Google Docs, Padlet, Kahoot, Zoom, etc.) enhances interactivity and brings practical relevance to the learning process. The article provides strategic approaches for effectively organizing the pedagogical training of future teachers, fostering professional reflection, and strengthening communicative competencies.